Significados de la categoría soldado herido y cuerpo apto en el batallón de sanidad soldado José María Hernández, una unidad de atención médica y de rehabilitación integral para los soldados del Ejército Nacional de Colombia (2017)
This monography presents an etnographic description of Batallón de Sanidad Josú María Hernández,a center for medical attention and physical and psychological rehabilitation. It also explores the meanings of wounded soldier and capable body among the soldiers that receive treatment in this institution.